The Magic WAND-functional overview. - Mikkonen, J.
The Magic WAND project (Wireless ATM Network Demonstrator) is one of the largest projects within the European Union ACTS (Advanced Communications Technologies and Services) initiative. The project aims to design, verify, implement, and demonstrate a wireless access network for ATM LAN's. The complete range of functionality, from physical data transmission to shared multimedia application, is addressed. The WAND system is designed for indoor environments with user mobility limited to walking speed. The system's functional specification has been designed and verified using SDL (specification and description language). In this paper, the WAND system functional model is given and SDL simulation results are presented, to illustrate how the protocols support some of the key operations of a wireless access network. These include initial registration, call setup, and handover
Keywords: ATM LAN; European Union ACTS initiative; Magic WAND; SDL simulation; Call setup; Design; Functional model; Functional overview; Functional specification; Functionality; Handover; Indoor environments; Initial registration; Key operations; Physical data transmission; Protocols; Shared multimedia application; User mobility; Walking speed; Wireless ATM network demonstrator; Wireless access network